5x=x+t

Simple and best practice solution for 5x=x+t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x=x+t equation:


Simplifying
5x = x + t

Reorder the terms:
5x = t + x

Solving
5x = t + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5x + -1x = t + x + -1x

Combine like terms: 5x + -1x = 4x
4x = t + x + -1x

Combine like terms: x + -1x = 0
4x = t + 0
4x = t

Divide each side by '4'.
x = 0.25t

Simplifying
x = 0.25t

See similar equations:

| 9X+5Y=-56 | | X+xy+y=21 | | 3x+8=-4+71 | | 7=-3-4b | | 5u+5(1-6)=u+8 | | 5x-3=6x+2x-9 | | 2cos^2(x)-sin(x)=0 | | 4*ln(x)-x=6 | | -3+6=2x-9 | | X^5/3=0.5 | | 10x-7(3)=-18 | | 17a-4= | | 4(3x-8)=28 | | 16y-10=14 | | 1/3(6x=2x | | 8x+8=3x+73 | | 3ln(2x+1)-5=1 | | (3x-x)+(8x+9)= | | x^3-2x^2+36=0 | | 4(5x-8)-13x=24 | | (12y*12y-144)=(3y*3y) | | x^2+(6x+17)=0 | | n+6-2=1 | | 2+c-3=3 | | X^4-3x^2+4x-6=0 | | F(x)=-3x+5 | | (cd+2)+cd-4= | | x^2-(m+1)x-5=0 | | (8x+4)=(5x+2) | | Sinx=0.75 | | 2a+16+b=18+b | | 9x+26x^2=3 |

Equations solver categories